UPAYA MENINGKATKAN HASIL BELAJAR SISWA KELAS 4 SD DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE TGT (TEAMS GAME TOURNAMENT) BERBANTUAN MEDIA AJAR KARTU SOAL PADA MATA PELAJARAN IPAS MATERI BAGIAN TUBUH TUMBUHAN DI SDN GROBOGAN 02: PENELITIAN TINDAKAN KELAS (PTK) - Salsabilla Putri; Inna Fareza; Melik Budiarti, S.Sos, M.A. (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to improve the learning outcomes of fourth-grade students at SDN Grobogan 02 in the science subject, focusing on the material plant body parts, through the application of the Teams Games Tournament (TGT) cooperative learning model, assisted by question card teaching media. The background of the study is based on the low achievement of the Minimum Completion Criteria (KKM) and the dominance of the lecture method which makes students passive in learning. This study uses the Classroom Action Research (CAR) method in two cycles. The results of the study indicate that the application of the TGT model, aided by question card media, can significantly improve student learning outcomes, encourage active participation and foster critical and collaborative thinking skills.